Aerospace series. Connectors, electrical, rectangular, with sealed and non-sealed rear, plastic housing, locking device, operating temperatures - 55 °C to 175 °C. Cable clamp. Product standard Part 007, (31st December 2014) - British Standards Institution,
No abstract available